A nonlinear dynamic uniaxial strength criterion that considers the ultimate dynamic strength of concrete. (May 2017) - Lu, Dechun; Wang, Guosheng; Du, Xiuli; Wang, Yang
Highlights: A dynamic uniaxial strength criterion for concrete is proposed. The physical mechanisms governing the strain rate effect are given to describe the dynamic strength properties of concrete. The proposed criterion is capable of describing the actual dynamic strength and reflecting the ultimate dynamic strength of concrete. The recommended parameters are obtained to predict the strength of concrete that lack dynamic test data. Abstract: The existing test results and semi-empirical equations of the rate-dependent concrete strength have overestimated the actual dynamic strength because they do not distinguish between the actual dynamic strength related to the strain rate effects and the additional resistance caused by inertial effects. However, an ultimate strength of concrete exists at a strain rate exceeding a certain value. This paper proposes a nonlinear dynamic uniaxial strength criterion for concrete based on an analysis of the physical mechanisms governing the strain-rate-dependent behavior of concrete strength. The proposed criterion is able to describe the actual dynamic strength and to reflect the ultimate strength at a high strain rate of concrete. The results from two groups of dynamic uniaxial compressive tests and two groups of dynamic uniaxial tensile tests are used to verify the criterion. Moreover, the recommended physical parameters in the criterion are obtained by analyzing the statistical test results of dynamic uniaxial compression and tension. The recommended parameters can be used in the criterion to study the dynamic strength of concrete when dynamic tests are not feasible, and to predict the dynamic strength at high strain rates when tests are performed at lower strain rates.